Efficient Construction of Well‐Defined Multicompartment Porous Systems in a Modular and Chemically Orthogonal Fashion. (6th March 2017) - Gao, Ning; Tian, Tian; Cui, Jiecheng; Zhang, Wanlin; Yin, Xianpeng; Wang, Shiqiang; Ji, Jingwei; Li, Guangtao
Abstract: A microfluidic assembly approach was developed for efficiently producing hydrogel spheres with reactive multidomains that can be employed as an advantageous platform to create spherical porous networks in a facile manner with well‐defined multicompartments and spatiotemporally controlled functions. This strategy allows for not only large scale fabrication of various robust hydrogel microspheres with controlled size and porosity, but also the domains embedded in hydrogel network could be introduced in a modular manner. Additionally, the number of different domains and their ratio could be widely variable on demand. More importantly, the reactive groups distributed in individual domains could be used as anchor sites to further incorporate functional units in an orthogonal fashion, leading to well‐defined multicompartment systems. The strategy provides a new and efficient route to construct well‐defined functional multicompartment systems with great flexibility and extendibility.